GE_GERICHTE P/6951/2025 vom 29. August 2025 - GE Cour de justice (2025)
ORDONNANCE DE NON-ENTRÉE EN MATIÈRE;QUALITÉ POUR AGIR ET RECOURIR;AUTOMOBILE;VENTE;LEASING;ABUS DE CONFIANCE | CPP.115; CO.184; CPP.310; CP.138